2013
DOI: 10.4284/0038-4038-2012.268
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Chaos: Terrorist Target Choice Following Natural Disasters

Abstract: This article explores the differences between transnational and domestic terrorism, further differentiating by private versus government targets, to estimate the effect of exogenous catastrophic shocks on a country's level of domestic and transnational terrorism. The empirical analysis uses detailed data on terrorism, natural disasters, and other relevant controls for 176 countries from 1970-2007 to illuminate several key disparities in a postdisaster target choice of terrorists. The results indicate that natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…More importantly, attention is being drawn to understand the consequences as this will help to shape global policy on acts of terrorism. The contributors to this literature, and their focus has being: terrorism and its consequences on foreign investment Bandyopadhyay et al, , 2015Efobi et al, 2015); terrorism and the labour force (Berrebi and Ostwald, 2014a); terrorism and economic development (Piazza, 2006); terrorism and the productivity of certain sectors in the country (Berrebi and Klor, 2010;Berrebi and Ostwald, 2013); terrorism and fertility rate (Berrebi and Ostwald, 2014b). …”
Section: Figure 1: Capital Flight In Comparison With Other External Fmentioning
confidence: 99%
“…More importantly, attention is being drawn to understand the consequences as this will help to shape global policy on acts of terrorism. The contributors to this literature, and their focus has being: terrorism and its consequences on foreign investment Bandyopadhyay et al, , 2015Efobi et al, 2015); terrorism and the labour force (Berrebi and Ostwald, 2014a); terrorism and economic development (Piazza, 2006); terrorism and the productivity of certain sectors in the country (Berrebi and Klor, 2010;Berrebi and Ostwald, 2013); terrorism and fertility rate (Berrebi and Ostwald, 2014b). …”
Section: Figure 1: Capital Flight In Comparison With Other External Fmentioning
confidence: 99%
“…We control for many other factors that might influence the two or act as mediators; however, there could potentially still be reason to believe that disasters induce dissimilar effects on labor force participation between men and women. The use of a second instrument, lagged terrorism in nearby countries, helps to assuage these concerns and the association of one country’s level of terrorism to its neighbors’ is quite significant (Enders, Sandler, and Gaibulloev 2011; Berrebi and Ostwald 2013). The similarity between the results for the two, very different, IV approaches further supports the causal relationship.…”
Section: Resultsmentioning
confidence: 99%
“…The second approach utilizes lagged terrorism incidence in neighboring countries as an instrument for a country’s level of terrorism. Empirical studies have shown that shocks to terrorism can influence levels of transnational and domestic terrorism in neighboring countries (Enders, Sandler, and Gaibulloev 2011; Berrebi and Ostwald 2013). Data on country borders and distances were obtained from the bilateral distance file created by the Centre d’Etudes Prospectives et d’Informations Internationales (CEPII; 2010).…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, attention is being drawn to understand the consequences as this will help to shape global policy on acts of terrorism. The contributors to this literature, and their focus has being: terrorism and its consequences on foreign investment Bandyopadhyay et al, , 2015Asongu et al, 2015;Efobi et al, 2015); terrorism and the labour force (Berrebi and Ostwald, 2014a); terrorism and economic development (Piazza, 2006); terrorism and the productivity of certain sectors in the country (Berrebi and Klor, 2010;Berrebi and Ostwald, 2013); terrorism and fertility rate (Berrebi and Ostwald, 2014b). This study is the first to relate these two strands of literature by using a sample from the African region for the period 1987 to 2008 as well as a variety of macroeconomic controls.…”
Section: Introductionmentioning
confidence: 99%